Application Of Selasi Model Based On Project Based Learning (PjBL) In Developing Children's Creativity - Nurfadlilah, Wuri Annisa; Zakarsi, Khamim; Yusuf, Hibanna (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2025)
The transformation of education in the modern era requires learning that innovates in solving problems in society. One of the kindergarten learning innovations in the independent curriculum is project-based STEAM (Science, Technology, Engineering, Art, and Mathematics) learning. This learning project adjusts the situation and conditions in the field, one of which is the SELASI (Art Collage Creation) model. The purpose of this study was to determine how the application of the SELASI model based on PJBL (Project Based Learning) in the development of children's creativity at Amal Insani Kindergarten Yogyakarta. This research uses qualitative research based on field study at Amal Insani Kindergarten Yogyakarta which is supported by other literature sources. This research data collection technique includes three stages, namely interviews, observation and documentation to explore more in-depth information. The results of this study indicate that the SELASI model based on PJBL can develop children's creativity at Amal Insani Kindergarten Yogyakarta. The findings in this study are that the PJBL-based SELASI model not only increases children's creativity but also trains children's independence in solving problems through children's knowledge and experience.